A Study on assimilation in culture and tradition of community at Kampung Gagu Jelebu Negeri Sembilan / Nurul Shima Taharuddin and Mohamad Khalil Amran - Nurul Shima, Taharuddin; Mohamad Khalil, Amran (Universiti Teknologi MARA, Perak, 2018)
The purpose of this research is to study and to understand the assimilation that happen to Minangkabau ethnic that live in kampung Gagu, Jelebu Negeri Sembilan. The aim of this study is to identify the assimilation that happens to social life of Minangkabau ethnic in Kampung Gagu, Jelebu negeri Sembilan. Assimilation that happen to culture has giving a big change to the dynamic process whereby the living cultures of the world are changing and adapting to external or internal forces. This process is occurring within western culture as well as non-western and indigenous cultures of the world. Forces which contribute to the cultural change is technological, socio culture, migration and economic. Base on method that collected from interview and photo documentation, this study has come out with a result that factor contribute to the various formation of culture Minagkabau ethnic in kampung Gagu is because of development of economy. This factor speeded up the process of the eradication of all the Adat culture, except for its weak and powerless political structure and organisation